Optimal Control Strategy of Coupler Force in Urban Rail Transit - JING Feiyao; XU Gang; YIN Jian; SHEN Jianhao (机车电传动)
Based on two kinds of operating conditions: constant speed motion and constant force start motion, the relationship between the coupler force and the traction force was analyzed by establishing a multi-particle urban rail transit simulation model in the background of the Shenzhen metro line1 in order to optimize the coupling force between the trains. According to the simulation results of the coupler force, the standard of the evaluation of the coupler force was proposed and the reasonable control strategy of the train was obtained. In the meantime, two models of parallel experiments, rational traction force grouping and mathematical statistics were used to draw the experimental conclusion. Therefore, the validity of the simulation experiment was verified relying on train calculation and comparison of simulation results. Experimental results showed that under the precondition of satisfy the standard of metro vehicle running, starting and accelerating the train in the constant force and constant speed operation, the optimal control strategy was not train traction evenly distributed control strategy. Meanwhile, the train optimal control mode could be obtained.